Digital Flipbook-Based Teaching Material for Writing Poetry in Elementary School - Fauzi Gusman; Seni Apriliya; Ahmad Mulyadiprana (Indonesian Journal of Primary Education, 2021)
This study was conducted to solve the problem of children's difficulties in writing poetry in fourth grade by using digital teaching materials to write poetry in a form of flipbook. The purpose of this research is to design a flipbook-based digital teaching material product to facilitate learning to write poetry in elementary schools, especially in Grade IV. The method used was Educational Design Research (EDR) starting from analyzing needs according to problem identification and exploring what was found in elementary schools, design and construction of developed tools, to evaluation and reflection of developed tools. The results of developing digital teaching materials for writing poetry were contents that can be taught to fourth grade elementary school students including: (1) The concept of poetry, (2) Basic poetry, (3) Elements of poetry, (4) Looking for ideas, (5) Pouring ideas in the form of poetry that is supported by multimedia provided by flipbook so that the digital teaching material for writing poetry based on flipbook developed by researchers are suitable to use. Thus, digital teaching material for writing poetry in the form of a flipbook can meet the needs of learning to write poetry in elementary schools because there are multimedia such as animation, images, videos, and audio so that learning can be supported and more interesting by utilizing the sophistication of existing technology. The position of this digital teaching material is as an additional reference in learning literature in elementary schools.